The moral psychology handbook - Doris, John M. (John Michael), 1963-; Cushman, Fiery; Moral Psychology Research Group (Oxford : Oxford University Press, 2010)
'The Moral Psychology Handbook' offers a comprehensive discussion of how the human mind influences, and is influenced by, human morality. Each chapter is a collaborative effort covering major issues in moral psychology, written by leading researchers in both philosophy and psychology.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Moral development; Ethics; Psychology -- Philosophy